Detektor Kondisi Tingkat Kelembaban Tanah pada Tanaman Hias Menggunakan Nodemcu Esp8266 Berbasis IoT - Syam Ramadhan; M Iwan Wahyuddin; Rini Nuraini (KITA Institute, 2022)
Technological developments in the era of Globalization, are widely used in various fields, one of the developing technologies is the technology on the NodeMcu ESP8266. In the Soil moisture Detector System in Ornamental Plants Using the IoT-Based NodeMcu ESP8266, based on the problem factors that exist in a failure in plant growth, it is very influential in terms of technique and also improper plant watering procedures, can cause plant growth to be disrupted and also withered. To overcome this problem, the author designed a Moisture Condition Detector in Ornamental Plants Using an IoT-Based NodeMcu ESP8266. Where this system can run commands to automatically water plants from soil moisture while simultaneously watering manually with various desired conditions and the system can send notifications that users can receive via telegram. Through the Moisture Level Condition Detector system in this ornamental plant, it can increase the level of effectiveness, so the quality that the plants get will be better maintained.